Impact of extensive negative pressure wound therapy on neonatal respiration: A case report. Issue 10 (25th October 2021) - Osawa, Ichiro; Tsuboi, Norihiko; Nosaka, Nobuyuki; Nishimura, Nao; Nakagawa, Satoshi
Abstract: An extensive topical negative pressure wound therapy (NPWT) from the abdominal to chest walls in neonates may decrease the compliance of the chest wall. Therefore, it is important to monitor respiratory function carefully during the procedure. Abstract : An extensive topical negative pressure wound therapy (NPWT) from the abdominal to chest walls in neonates may decrease the compliance of the chest wall. Therefore, it is important to monitor respiratory function carefully during the procedure.